2022
DOI: 10.1021/acs.chemrev.1c00963
|View full text |Cite
|
Sign up to set email alerts
|

Phenalenyl Radical: Smallest Polycyclic Odd Alternant Hydrocarbon Present in the Graphene Sheet

Abstract: Phenalenyl, a zigzag-edged odd alternant hydrocarbon unit can be found in the graphene nanosheet. Hückel molecular orbital calculations indicate the presence of a nonbonding molecular orbital (NBMO), which originates from the linear combination of atomic orbitals (LCAO) arising from 13 carbon atoms of the phenalenyl molecule. Three redox states (cationic, neutral radical, and anionic) of the phenalenyl-based molecules were attributed to the presence of this NBMO. The cationic state can undergo two consecutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 376 publications
4
60
0
Order By: Relevance
“…Consequently, compound 4b might be categorized as aminyl radical, even though the unpaired electron is highly delocalized to the three nitrogen atoms and to a lesser extent to the naphthalene backbone and phenyl units. Similar stabilization was found in the carbocyclic analogue of 4b  aphenalenyl radical; although in that case, the spin density is evenly distributed along the π-system …”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Consequently, compound 4b might be categorized as aminyl radical, even though the unpaired electron is highly delocalized to the three nitrogen atoms and to a lesser extent to the naphthalene backbone and phenyl units. Similar stabilization was found in the carbocyclic analogue of 4b  aphenalenyl radical; although in that case, the spin density is evenly distributed along the π-system …”
Section: Resultssupporting
confidence: 66%
“…Similar stabilization was found in the carbocyclic analogue of 4b� aphenalenyl radical; although in that case, the spin density is evenly distributed along the π-system. 24 Since radical 4b exhibited high stability, we attempted to crystalize it for its solid-state characterization. However, slow evaporation of the toluene solution of 4b resulted in the crystallization of its dimer�compound 5 (Scheme 6a and Figure 3).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A similar observation was noted in previously reported PLY-based radical species after chemical reduction of the metal-PLY complexes. [38][39] The green compound (1A) was characterized with HRMS and EPR spectroscopy. The mass data recorded under strict inert conditions indicate no structural change in the reduced species.…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
“…The redox‐active phenalenyl (PLY) molecule, a well‐known building block in material sciences, functions as an electron reservoir using its low‐lying nonbonding molecular orbital (NBMO) [35–37] . Using this property of PLY, during the past decade, our group has developed several efficient Earth‐abundant metal catalysts bearing PLY‐based ligands for various organic transformations following a radical pathway, and this area has been reviewed recently [38] . In this work, with the help of experimental and theoretical studies, we have demonstrated an unusual metal‐ligand cooperative approach for executing this reductive functionalization of CO 2 with amides, where a ligand‐centred radical plays a crucial role in initiating the process.…”
Section: Introductionmentioning
confidence: 99%
“…Phenalenyl is a very well-known aromatic polycyclic hydrocarbon that can act as an electron carrier, and it can store sequentially two electrons without completely destroying the aromaticity of the individual phenyl rings . The first reduction of phenalenyl cation leads to the monoreduced phenalenyl radical, while the second reduction leads to doubly reduced anionic species. The open-shell monoreduced PLY radical species (13πes system) has been extensively utilized in the construction of molecular battery, electroconductor or molecular switch, , and spin memory device, and this topic has been reviewed recently. Implementation of the monoreduced PLY radical species as a catalyst for various reactions was accomplished recently. In the present work, we devise a strategy for the generation of di-reduced phenalenyl using an organic electron donor (OED). This di-reduced phenalenyl species was used as a super electron donor to activate the strong aryl-halide bond generating aryl radical, which we strategize to use for coupling with amines at room temperature (Figure b) to accomplish Buchwald–Hartwig-type coupling reactions.…”
Section: Introductionmentioning
confidence: 99%